Spatial variation of traffic accidents in Maysan Governorate for the year 2018 - هديل هشام عبد الامير , م.م. (lark, 2020)
Spatial variation of traffic accidents in MaysansTraffic accidents are one of the most prominent problems that human societies suffer from, because they have become one of the causes of innocent people deaths, as they drain a lot of money and human energies that can be invested in other areas and have a great benefit for members of society, so this study came to stand On the most important causes and factors that led to the occurrence of traffic accidents, the distribution of the places of their occurrence and their preparation on the districts of the governorate, in addition to studying some indicators of risk and the consequences resulting from them and analyzing the data related to the characteristics of the accidents by referring to the reports of traffic accidents in the governorate for the year (2018) and drawing conclusions that show the size of these accidents and what Recommendations that may reduce the severity of these accidents .